Prevalence of refractive errors among school children in the rural field practice area of a tertiary care hospital, Bengaluru - Vidusha, Karavadi Sri Sai; M. N., Damayanthi (International Journal Of Community Medicine And Public Health, 2018)
Background: An estimated 19 million children are visually impaired, and 12 million are visually impaired due to refractive errors. Children fall in preventable age group for correction of refractive errors. Schools are best forum for implanting health education for children and for early detection of ocular morbidity. This study was undertaken to assess the prevalence of refractive errors among school children in rural field practice area of Rajarajeswari Medical College and Hospital, Bengaluru. Methods: A cross sectional study was conducted among the schools in rural field practice area of Rajarajeswari Medical College and Hospital School children aged between 7-16 years were examined for defective vision using Snellens chart. General information of the children was collected using pre-designed and semi- structured questionnaire a. Children with abnormal vision were referred to hospital. Data was analyzed using SPSS software. Descriptive statistics was used and chi-square test of significance was applied. Results: 1140 study subjects were examined out of which 577 (50.6%) were females and 563 (49.4%) males. The mean age was 11.28 years. The prevalence of refractive errors was 10.5%.The prevalence of refractive errors was significantly associated with age (p<0.05). The prevalence of myopia, hypermetropia and astigmatism in study subjects was 58.5%, 17.1%, 24.4% respectively. Conclusions: The prevalence of refractive errors, especially myopia, was higher in older children. Causes of higher prevalence and barriers to refractive error correction services and compliance should be identified and addressed. Eye screening of school children is recommended.